Analisis dan Perancangan Sistem Informasi Kepegawaian PT.Indometal Mitrabuana - Lareno Nurfadillah; Djoko Pramono; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Indometal Mitrabuana is located in jl.angsana raya block 16 no. 1B Delta Silicon industrial estate 1 Cikarang, Bekasi, West Java. This company is engaged in the supply of raw steel material processing services. HRD department of PT. Indometal Mitrabuana is one of most important department that manages human resources. Reporting is certainly one of core activities of this department. However by using manual data collection there is often a loss of data, information that is not up-to-date and inefficient of information notification. Given an information system that focuses on managing employee data, it can maximize the activity of reporting human resources optimally, thus conducted a research with Ripple methodology that will produce requirements and system design both in terms of business and systems which prodeuce use case business and use case diagrams in the requirement phase , In analysis phase will generated analysis class diagram and communication diagram, design phase will generate class diagrams, sequence diagrams, and database schema. Every requirement and feature will be tested using Traceability matrix, whether every requirement has a unique code and can be track back into all requirement.